New species of Eugenia (Myrtaceae) from São Paulo state, Brazil - Mazine, Fiorella F.; Meireles, Leonardo Dias; Sobral, Marcos; Valdemarin, Karinne Sampaio (Phytotaxa, 2017)
Three species of Eugenia from São Paulo state’s Atlantic forest are described, illustrated, compared with related species and commented in their conservation issues: Eugenia binata, from Ilhabela, is close to Eugenia lomeroensis, from which can be distinguished by larger leaf blades, larger flower buds, and densely pubescent ovary; Eugenia pithecocephala, from Peruíbe, is close to Eugenia grandissima, from which can be distinguished by the smaller leaves and costate fruits with five seeds; and Eugenia sulcatifolia, from Ubatuba, is close to Eugenia umbrosa, from which can be distinguished by the broader leaf blades, obovate bracteoles and slightly costate ovary.